Effects of different light wavelengths from LEDs on oxidative stress and apoptosis in olive flounder (Paralichthys olivaceus) at high water temperatures. (August 2016) - Kim, Bong-Seok; Jung, Seo Jin; Choi, Young Jae; Kim, Na Na; Choi, Cheol Young; Kim, Jae-Woo
Abstract: We investigated how different light spectra affect thermal stress in olive flounder ( Paralichthys olivaceus ), using light emitting diodes (LEDs; blue, 450 nm; green, 530 nm; red, 630 nm) at two intensities (0.3 and 0.5 W/m 2 ) at relatively high water temperatures (25 and 30 °C, compared to a control condition of 20 °C). We measured the expression and activity of antioxidant enzymes, superoxide dismutase (SOD) and catalase (CAT), and the levels of plasma hydrogen peroxide (H2 O2 ) and lipid peroxidation (LPO). Furthermore, the levels and mRNA expression of caspase-3 were measured, and terminal transferase dUTP nick end labeling (TUNEL) assays of liver and comet assays were performed. The expression and activity of antioxidant enzymes, as well as plasma H2 O2 and LPO levels were significantly higher after exposure to high temperatures, and significantly lower after exposure to green and blue light. Caspase-3 levels and mRNA expression showed a similar pattern. The TUNEL assay showed that apoptosis markedly increased at higher water temperatures, compared with the 20 °C control. In contrast, green light irradiation decreased apoptosis rate. Furthermore, the comet assays showed that nuclear DNA damage was caused by thermal stress, and that green light irradiation played a role in partially preventing this damage. Overall, these results suggest that light with green and blue wavelengths can reduce both high temperature-induced oxidative stress and apoptosis, and that particularly green light is efficient for this. Therefore, green light can play a role in protecting in olive flounder from thermal stress damage. Highlights: Thermal stress causes DNA damage and apoptosis in olive flounder. Green light irradiation can prevent this stress-induced DNA damage. Red light irradiation increases DNA damage patterns and apoptosis.